Dynamic response of stiffened plate under internal blast: Experimental and numerical investigation. (May 2021) - Li, Ying; Ren, Xianben; Zhao, Tian; Xiao, Dengbao; Liu, Kai; Fang, Daining
Abstract: Stiffened plates are the basic units of ships, aircraft and other structures. The purpose of this paper is to investigate the dynamic response of stiffened plates under internal blast loading. A combined experimental and numerical investigation was carried out on the cabin structures with unstiffened, single-stiffened and double-stiffened plates. The characteristics of internal blast wave, the effects of stand-off distance and the stiffener position on the deflection and failure modes of stiffened plates were sequentially analyzed. It was interestingly found that the deflection first decreased and then increased with the increase of stand-off distance. Additionally, despite of the reinforcement on the deformation resistance, the stiffeners tended to reduce the damage tolerance of the target plates. This research provides the basic data and theoretical support for the blast resistance design of ships, aircraft and other structures. Highlights: Experimental study was carried out to investigate dynamic response of stiffened plates under internal blast. The effects of blast distance and stiffener on the deflection and failure modes of stiffened plates were analyzed. The deflection first decreased and then increased with the increase of stand-off distance.